Analisis Sektor Unggulan Untuk Pembangunan Ekonomi Di Kabupaten Pesawaran - Weliza Weliza; Agus Hudoyo; Muhammad Irfan Affandi (Politeknik Negeri Lampung, 2021)
This study aimed to analyze the leading sectors for economic development in Pesawaran Regency. The data used is secondary data, namely the Gross Domestic Regional Products (GDRP) and the Input-Output Table. These data were analyzed using the Location Quotient (LQ) method, Shift-share analysis, and Input-Output analysis. The results of the analysis revealed that the leading economic sectors that drive the economy in Pesawaran Regency were wholesale and retail trade; wood industry, goods from wood and cork and woven goods from bamboo, rattan and the like; horticulture; construction; plantation; and fisheries. Keywords: Location Quotient, Shift-Share Input-Output, Leading Sector.